Developing connections + Junction City, Kansas - Rolfs, Brett T. (Kansas State University, 2009)
This project is of a personal interest to me, because Junction City, Kansas has been my home town since birth. The city is a rapidly growing community with a strong military presence from nearby Fort Riley, Kansas. The project will explore the capacity for effective growth while preventing the degradation of fragile natural resources within the community. It will also provide new amenities for the people of Junction City as well as capitalize on the existing natural amenities. The project provides storm water management solutions for an existing retail development and a proposed mixed use development incorporating sustainable practices. Studying the history and progressive nature of Junction City provides an understanding of how to embrace the design within the surrounding landscape. A model for responsible mixed use retail and residential development in Junction City is provided through this project. Storm water best management strategies were also implemented to improve the oxbow wetlands by capturing the first flush storm event as well as a 25 year storm event. Finally, the project should continue to shape the history and enthusiasm of Junction City and its people.
Developing connections and Junction City, Kansas
Developing connections plus Junction City, Kansas
Keywords: Stormwater; Best management practice; Retrofit; Landscape Architecture (0390)